ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MEMECAHKAN SOAL OPEN ENDED BERDASARKAN TAHAP BERPIKIR VAN HIELE - Nur Hidayati Laili; Khafidhoh Nurul Aini; Erik Dwi Utami (INSPIRAMATIKA, 2020)
This study aims to find out how students' critical thinking skills in solving Open Ended problems based on Van Hiele's thinking stage. This research is a descriptive qualitative study. The subjects of this study were 6 students of VII-E grade at SMP Negeri 5 Lamongan in the 2019/2020 academic year. The determination of the subject was based on the results of the VHGT (Van Hiele Geometry Test) test. The instrument that was given to the research subjects consisted of a description test consisting of 2 questions. The data used are test results and the results of interview interviews. Based on the analysis of the data that has been done, the results of this study indicate that: (1) the ability of students to think critically with visualization thinking (stage 0) has TKBK 2 or sufficiently critical, which means students are able to meet 2 indicators of critical thinking skills, namely clarification and assessment. (2) the ability of students to think critically with the stage of analytical thinking (stage 1) has a TKBK of 3 or critical, which means students are able to meet 3 indicators of critical thinking skills, namely clarification, assessment and inference. (3) the ability of students to think critically with the stage of informal deduction thinking (stage 2) has TKBK 4 or very critical, which means students are able to meet all the indicators of critical thinking skills namely clarification, assessment, inference and strategy.